Aspergillus mediastinitis after cardiac surgery. (March 2016) - Caballero, Marie-Josée; Mongardon, Nicolas; Haouache, Hakim; Vodovar, Dominique; Ben Ayed, Issam; Auvergne, Lauriane; Hillion, Marie-Line; Botterel, Françoise; Dhonneur, Gilles
Highlights: Aspergillus mediastinitis is a very rare complication after cardiac surgery. The prognosis is extremely poor, both in immunocompetent and immunocompromised patients. Culture-negative or indolent sternal wound infection should suggest this complication. Optimal treatment relies on surgical debridement and antifungal therapy. Antifungal treatment should include amphotericin B or voriconazole. Summary: Background: Mediastinitis is a serious complication after cardiac surgery. While bacteria are the more common pathogens, fungal infections are rare. In particular, several cases of postoperative Aspergillus mediastinitis have been reported, the majority of which had an extremely poor outcome. Methods: A case of mediastinitis in a 42-year-old patient due to Aspergillus fumigatus after cardiac surgery is described. Two main risk factors were found: cardiogenic shock requiring veno-arterial extracorporeal life support and failure of primary closure of the sternum. A full recovery was attained after surgical drainage and antifungal therapy with liposomal amphotericin B, followed by a combination of voriconazole and caspofungin. The patient was followed for 18 months without relapse. Results: This is an extremely rare case of postoperative Aspergillus mediastinitis exhibiting a favourable outcome. Based on a systematic review of the literature, previous cases were examined with a focus on risk factors, antifungal therapies, and outcomes. Conclusion: The clinical features of postoperative Aspergillus mediastinitis may be paucisymptomatic, emphasizing the need for a low index of suspicion in cases of culture-negative mediastinitis or in indolent wound infections. In addition to surgical debridement, the central component of antifungal therapy should include amphotericin B or voriconazole.